CAN BRAIN EDEMA BE PREDICTED WITH OPTIC NERVE SHEATH DIAMETER MEASUREMENT IN CASES WITH DIABETIC KETOACIDOSIS?: A PRELIMINARY STUDY - Özlem Tolu Kendir; Hayri Levent Yılmaz; Nilgün Erkek; Sinem Sarı Gökay; Rıza Dinçer Yıldızdaş; Bilgin Yüksel (İstanbul Tıp Fakültesi Dergisi)
Objective: The clinical signs and symptoms of brain edema resulting from diabetic ketoacidosis (DKA) may not always be ob vious. When the intracranial pressure increases, the optic nerve sheath diameter (ONSD) simultaneously increases and can be imaged with ultrasonography. We aimed to discuss the determinative features of ONSD measurements in brain edema (BE) in DKA. Materials and Methods: Patients who were classified as having mild, moderate and severe DKA were included in the study. Transorbital ultrasonography was performed during the first two hours of treatment while the patients remained in the supine neutral position with their eyes closed. The optic nerve sheath diameters, which appeared as a hypoechoic double-edged line 3 mm deep to the globe, were measured. The same measurements were repeated in outpatient clinic controls. The ONSD values and metabolic, neurological conditions of the patients were compared. Results: Eight patients with a mean age of 8.8±3 (Standard Deviation (SD)) years were included in the study. Seven of them presented with moderate to severe DKA. Two patients suffering from headaches were found to have mild BE according to the brain computerized tomography (CT). The ONSD was 5.7±0.93 mm (mean±SD) in the patients with moderate-severe DKA and 4 mm in the single patient with mild DKA. The ONSDs of the two patients with BE on the CT were 6.8 mm and 5.9 mm. The mean ONSD of the five patients with severe DKA was 4.4±0.32 mm in the outpatient clinic checks. Conclusion: The measurement of ONSD by USG may be a supportive method for predicting BE in children with DKA.